Efficient synthesis of isoindolones by intramolecular cyclisation of pyridinylbenzoic acids. Issue 37 (3rd September 2021) - Solea, Atena B.; Wang, Sining; Xue, Xiao-Song; Crochet, Aurelien; Fromm, Katharina M.; Houk, Kendall N.; Mamula, Olimpia; Allemann, Christophe
Abstract : Instead of anhydrides, isoindolones are formed in excellent yields by the deprotonation and tosylation of 2-pyridinylbenzoic acids. The mechanism of this new intramolecular cyclisation has been studied by DFT calculations. Abstract : A straightforward one-pot method for the synthesis of unreported pyrido-[2, 1- a ]isoindolones in excellent yield is described. Two novel isoindolones were synthesized and fully characterized. The alkyl substituents on the pyridine play an important role in the outcome of the reaction. The mechanism, investigated through DFT calculations, features an unprecendented intramolecular cyclization reaction involving a carboxylic acid activated by tosyl chloride and an electron-poor pyridinic nitrogen. This protocol completes the known strategies to obtain functionalized isoindolones.